2021
DOI: 10.11113/sh.v13n2-3.1917
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review on The Factors That Influence Well-Being Among Teachers

Abstract: Increasing the well-being of teachers in schools is an important issue that needs to be discussed. Nowadays, there are many problems related to the teacher, which will affect the teacher's professionalism in teaching. This systematic review aims to synthesize factors that can impact teacher welfare. The journal search database includes EBSCOHOST, PROQUEST, EmeraldInsight, and ScienceDirect, published in the last ten years (2010-2019). The keywords used are "Welfare" OR "Psychological Welfare" OR "Subjective We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Capitalizing on previous systematic review studies reported on TWB, e.g., [94], the selected studies that satisfied the inclusion criteria were accordingly categorized based on available evidence to map out the key conceptual themes in the relevant research. Identification and classification of emergent and major themes pertinent to the objective of this review were possible using the inductive thematic analysis approach [95] in terms of (a) TWB status amidst the COVID-19 era, (b) TWB stressors and coping strategies used by educators in their effort to mitigate the negative impact of the pandemic on their overall personal and professional welfare, and (c) research trends used in TWB investigations during the COVID-19 years.…”
Section: Data Collection and Data Analysismentioning
confidence: 99%
“…Capitalizing on previous systematic review studies reported on TWB, e.g., [94], the selected studies that satisfied the inclusion criteria were accordingly categorized based on available evidence to map out the key conceptual themes in the relevant research. Identification and classification of emergent and major themes pertinent to the objective of this review were possible using the inductive thematic analysis approach [95] in terms of (a) TWB status amidst the COVID-19 era, (b) TWB stressors and coping strategies used by educators in their effort to mitigate the negative impact of the pandemic on their overall personal and professional welfare, and (c) research trends used in TWB investigations during the COVID-19 years.…”
Section: Data Collection and Data Analysismentioning
confidence: 99%
“…The teacher’s occupational well-being is a positive state of health when his/her expectations are balanced by the needs of students: the teacher is satisfied with his/her work and systematically achieves his/her goals by collaborating with students and colleagues ( Na’imah et al, 2021 ). Mental health is an important component of psychological well-being.…”
Section: Introductionmentioning
confidence: 99%
“…The predictors of KG teachers’ mental well-being can be divided into personal, professional, and organizational ( Na’imah et al, 2021 ). The most important personal factors are demographic variables such as marital status and age ( Koulierakis et al, 2019 ), self-efficacy, and self-confidence ( Bermejo-Toro et al, 2016 ); the most relevant professional factors are experience, knowledge, skills, and workload ( Na’imah et al, 2021 ); the most significant organizational factors are the work environment, salary level ( Koulierakis et al, 2019 ), organizational structure, and team climate ( Parent-Lamarche and Marchand, 2019 ). Low salaries, lack or insufficiency of benefits and social guarantees, difficult working conditions, and expectations that do not correspond to the real situation are some of the frequently reported stress moderators for KG teachers ( Faulkner et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%